2021
DOI: 10.3390/biomedicines9050451
|View full text |Cite
|
Sign up to set email alerts
|

Using Pharmacogenetics of Direct Oral Anticoagulants to Predict Changes in Their Pharmacokinetics and the Risk of Adverse Drug Reactions

Abstract: Dabigatran, rivaroxaban, apixaban, and edoxaban are direct oral anticoagulants (DOACs) that are increasingly used worldwide. Taking into account their widespread use for the prevention of thromboembolism in cardiology, neurology, orthopedics, and coronavirus disease 2019 (COVID 19) as well as their different pharmacokinetics and pharmacogenetics dependence, it is critical to explore new opportunities for DOACs administration and predict their dosage when used as monotherapy or in combination with other drugs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 101 publications
0
30
0
3
Order By: Relevance
“…Similarly, other recent studies have confirmed the correlation between ABCB1 and CES1 SNPs and plasma levels of dabigatran in Chinese patient populations [14]. Recent additional reviews of literature do not add much to what has been previously described [15,16].…”
mentioning
confidence: 73%
“…Similarly, other recent studies have confirmed the correlation between ABCB1 and CES1 SNPs and plasma levels of dabigatran in Chinese patient populations [14]. Recent additional reviews of literature do not add much to what has been previously described [15,16].…”
mentioning
confidence: 73%
“…apixaban is also a substrate of P-gp transport proteins and breast cancer resistance protein (BCRP). Cytochrome P450 (especially CYP3A4/5) [ 40 , 41 ] and advanced age represent two of the contributing factors to the reduction in cytochrome P450 functionality [ 42 ]. However, we cannot exclude that an overexpression or an increase in CYP3A4/5 activity (on a genetic basis) significantly may have reduced apixaban levels in our patient, by inducing vascular thromboembolic microphenomena downstream.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacogenetics of DOACs affect their pharmacokinetic properties. Interindividual variability regarding the efficacy and safety profile of direct anticoagulants could be related to polymorphism of the genes responsible for pharmacokinetic processes (17). To date, several single nucleotide polymorphisms (SNPs) of genes coding the proteins participating in the metabolism of DOACs have been correlated with anticoagulant treatment response.…”
Section: Interaction Between Doacs Metabolism and Antiviral Therapymentioning
confidence: 99%